Keefektifan Teknik Self Instruction dalam Konseling Cognitive Behavior Counseling untuk Meningkatkan Efikasi Diri Sosial Siswa SMKN 2 Malang - Dewi, Fitri Aryadini; Atmoko, Adi; Triyono, Triyono (Jurnal Kajian Bimbingan dan Konseling, 2016)
This study aims to determine the effectiveness of self instruction technique in cognitive behavior counseling to improve the self efficacy in social relation of vocational students. This experimental study using Single Case Experimental Design (SCED) model of the A-B-A’. The subject of research are three students of SMKN 2 Malang which show a low level of self efficacy social based on the scale of self efficacy social. The research instrument used as scale self efficacy social with the validity > 0.3 and reliability 0, 883, observation guidelines, and counseling guidelines. The results showed that subjects experienced an increase in social self-efficacy after a treatment given. Data has been analyzed using a visual inspection showed significant changes, so that it can be concluded self-instruction techniques in cognitive behavioral counseling is effective to improve student’s social self-efficacy SMKN 2 Malang.